Salivary Biomarkers in Oral Squamous Cell Carcinoma: Current Perspectives and Challenges in their Clinical Application - Saba, Khan; Zareef, Uzma; Chughtai, Nadia; Imtiaz, Syed Ashar; Askary, S. Hussain; Askary, Gul Rukh; Haider, Shajia (Indus Journal of Bioscience Research, 2024)
Oral cancer is a life-threatening disease that predominantly affects the oral cavity, with approximately 90% of cases being oral squamous cell carcinomas (OSCC). Rapid metastasis and late detection are key factors contributing to the poor prognosis of OSCC. The alarming rise in OSCC-related mortality underscores the urgent need for clinical diagnostic methods that enable early detection. In recent years, salivaomics has gained popularity in molecular diagnostics due to the accessibility and non-invasive nature of saliva. Researchers have identified over 100 salivary biomarkers with potential roles in OSCC screening, categorized into proteomic, genomic, transcriptomic, and metabolic biomarkers. Although these biomarkers show high specificity and sensitivity, challenges such as variability and the need for standardized protocols must be addressed to improve diagnostic accuracy and treatment outcomes. This review explores significant salivary biomarkers in OSCC management and highlights the challenges that hinder their clinical application, emphasizing the need for optimized protocols to enhance test validity